Marketing para el posicionamiento del centro ecoturístico comunitario ¨Tinku¨ de la comunidad Inti Churi, cuidad de Guaranda, año 2024 - Quinatoa Mullo, Edwin Rolando (2024)
The purpose of this project is to develop marketing strategies for the positioning of the ecotourism center, located in the province of Bolivar, Canton Guaranda, Inti Churi community, on the old road to Riobamba. To achieve this, a methodology that combines qualitative and quantitative approaches was used, including the application of research instruments such as surveys, interviews and direct observation. These methods provide a clearer understanding of how the center operates. Marketing is a fundamental tool to build customer loyalty, increase visibility through different methods, therefore, it will help the resort to grow in sales and also to position itself in the mind of every tourist. Also, in the surveys conducted, it was found that most of them are women with an occupation of public and private servants, which possibly have an adequate economic condition and thus decide what they do in their free time and what tourist destinations they will visit. In addition, the respondents stated that they like to do tourism to relax, de-stress and entertain themselves in order to get away from their daily life, which is work. Ultimately, 5 matrices were used for the marketing plan: pestel matrix, prioritization matrix, competitive profile matrix, value chain matrix, and cross-cutting foda matrix. Based on these matrices, strategies corresponding to the marketing mix were developed, namely: product; creating tourist packages; price, attracting and building customer loyalty, location; agreement with the municipality for the ferry, promotion; communication strategies and seduction merchandising.